2017
DOI: 10.4103/ijccm.ijccm_24_17
|View full text |Cite
|
Sign up to set email alerts
|

Use of nutrition risk in critically ill (NUTRIC) score to assess nutritional risk in mechanically ventilated patients: A prospective observational study

Abstract: Context:Nutritional risk assessment must be done on all critically ill patients. Malnutrition in intensive care unit (ICU) patients is associated with adverse clinical outcomes. Traditional scoring systems cannot be used for screening in mechanically ventilated (MV) patients because these patients are unable to provide information on their history of food intake and weight loss. The Nutrition Risk in Critically ill (NUTRIC) score is the appropriate nutritional assessment tool in MV patients.Aims:This prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 13 publications
(17 reference statements)
9
54
1
5
Order By: Relevance
“…They found that the length of hospital stay and mortality rate are higher in patients with higher nutritional risks (mNUTRIC score ≥5) than in patients with lower mNUTRIC scores. We also found a similar correlation between mNUTRIC score and mortality in our study (10).…”
Section: Mendes Et Al Considered Patients Withsupporting
confidence: 90%
“…They found that the length of hospital stay and mortality rate are higher in patients with higher nutritional risks (mNUTRIC score ≥5) than in patients with lower mNUTRIC scores. We also found a similar correlation between mNUTRIC score and mortality in our study (10).…”
Section: Mendes Et Al Considered Patients Withsupporting
confidence: 90%
“…The NUTRIC score was developed in studies of critically ill patient populations and has been validated in many observational studies from different countries. 11,[14][15][16][17][18][19][20][21][22][23] As IL-6 is not routinely performed in most ICUs in the world, the modified-NUTRIC (mNUTRIC) score without IL-6 was proposed and revalidated. 14 However, one of the major limitations of the NUTRIC/mNUTRIC score is the absence of classical nutrition variables such as recent food intake and weight change.…”
Section: Nutrition Risk Screeningmentioning
confidence: 99%
“…The NUTRIC/mNUTRIC score has been shown in various critically ill populations to have good predictive validity for clinical outcomes, although the discriminative ability is of fair level (Table 1). 11,[14][15][16][20][21][22][23] Various observational studies in different populations have also shown that clinical outcomes are modified by nutrition adequacy depending on the risk status of the patients (Table 1). 11,14,[16][17][18][19] The NUTRIC/mNUTRIC score remains to be prospectively tested in a randomized controlled trial.…”
Section: Nutrition Risk Screeningmentioning
confidence: 99%
“…1 Kalaselvan et al, que estudaram apenas pacientes sob ventilação mecânica, encontraram um valor inferior ao nosso: 48,6% dos pacientes admitidos tinham um escore NUTRIC igual ou superior a 5. 10 A média do escore NUTRIC do trabalho de Kalaiselvan foi 4, inferior à média encontrada no estudo original de Heyland et al, que inicialmente validou o escore. 6 A média do nosso escore foi 5,0±1,9.…”
Section: Discussionunclassified
“…O trabalho de Kalaiselvan tinha uma média de SOFA no D1 de 6.7, o de Heyland, de 7, e o nosso de 8,4±4,6. 10,6 Nesse trabalho foi encontrada uma habilidade preditiva do NUTRIC de se relacionar com mortalidade através do ponto de corte de 5,0 (AUC (area under the ROC curve): 0,736; IC 95%: 0,628-0,844). O estudo de Heyland et al encontrou valor semelhante (AUC: 0,783) com o mesmo ponto de corte, analisando mortalidade de 28 dias.…”
Section: Discussionunclassified